Role of Organic and Phosphate Fertilizer on Growth and Yield of Groundnut - Supriyono, Supriyono; Aryani, Cholis Laila; Pardono, Pardono; Budiastuti, Maria Theresia Sri (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2025)
Efforts to increase groundnut productivity can be achieved by fertilizing with organic and phosphate fertilizers. This research aims to examine the role of organic and phosphate fertilizers on growth and yield of groundnut. The research was conducted at the Faculty of Agriculture UNS Jumantono, EMPT (Ecology and Plant Production Management) Laboratory, Soil Chemistry and Fertility Laboratory from December 2024 to March 2025. The research used a Randomized Complete Block Design (RCBD) with two factors and each repeated three times. The first factor is dose of organic cow manure fertilizer (0, 10, 20, 30 ton.ha-1) and second factor is dose of phosphate fertilizer (0, 75, 150, 225 kg.ha-1). The observed variables include initial soil analysis, growth, yield, plant tissue analysis, and nutrient uptake analysis. Observational data were analyzed using analysis of variance (ANOVA) at a 95% confidence significant, Duncan Multiple Range Test (DMRT) at a 95% confidence significant, regression tests, and Pearson correlation tests. The results showed that cow manure fertilizer with an optimum dose of 25.67 ton.ha-1 combined with 225 kg.ha-1 of phosphate fertilizer resulted in the early flowering age, namely 24.97 days after planting. Organic cow manure fertilizer 10 ton.ha-1 was able to increase the number of leaves, leaf area index, fresh weight of straw, number of pods, dry weight of pods, number of seeds per plant, and seed weight per plant of groundnut compared without organic cow manure fertilizer. Phosphate fertilizer 75 kg.ha-1 was able to increase the number of pods, dry weight of pods, and number of seeds per plant compared without phosphate fertilizer.